Quantum cascade laser measurements of CH4 linestrength and temperature-dependent self-broadening and narrowing parameters at 7.16 µm. (December 2021) - Li, Jidong; Ding, Yanjun; Li, Zheng; Peng, Zhimin
Highlights: 1 Linestrength, temperature-dependent self-broadening and narrowing parameters of 10 CH4 transitions near 7.16 µm were measured over a temperature range of 290 - 1050 K. 2 The self-pressure-shift coefficient was found to change signs from negative to positive with increasing temperature and the Frost's formula fit well its temperature dependence. 3 Several weak transitions excluded from the HITEMP database were observed at elevated temperatures with the line positions given in this work. Abstract: Absorption lineshapes for 10 CH4 transitions in the v 2 and v 4 band were measured at high-resolution in a thermodynamically-controlled optical cell using a quantum cascade laser near 7.16 µm. Linestrength, self-broadening, -narrowing, pressure-shift coefficients and their temperature dependence were recorded over a temperature and pressure range of 290–1050 K and 3–80 kPa, respectively. Voigt, Rautian, speed-dependent Voigt profiles were least-squares fit to the measured absorption spectra to determine the best-fit lineshape parameters. Significant collisional-narrowing and speed-dependent effects were observed but no line mixing behaviour was found in pure CH4 at the experimental conditions. The self-pressure-shift coefficients were found to change signs from negative to positive with increasing temperature and the Frost's formula fit well their temperature dependence for the studied transitions. The measured spectra provided tests of the CH4 line lists near 1397 cm −1 released in HITEMP 2020 and the recorded spectroscopic parameters compared well with the values in the database. Several weak transitions excluded from the HITEMP database were observed at elevated temperatures with the line positions given here. The analyses of uncertainties in all the measured spectroscopic parameters were also demonstrated in this work.